Penerapan Pembelajaran Konseptual Interaktif Berbantuan Media Cmaptools untuk Meminimalkan Miskonsepsi - Muliani, Desy Eka (Universitas Islam Negeri Raden Intan Lampung, 2019)
Abstract: This study is aimed to comparative analysis of quantity of misconception, then student’s attitude scale after applying conceptual interactive learning with cmaptools media. This research used quasy experiment with Randomized Control Group Pretest-Posttest design and descriptive methods. The research sample was class X9 dan X10 semester 2 of Senior High Scool at Cimahi. Instruments that used were concept understanding test with CRI, observation form, student’s attitude scale form. Based on CRI analysis, the result were experiment class has more less misconception than control class. The result of student’s attitude scale was almost of all students agree that applying conceptual interactive learning with cmaptools media can motivate, gain concept understanding and can be applied for another concept in physicsAbstrak: Penelitian ini bertujuan menganalisis perbandingan kuantitas miskonsepsi, serta deskripsi skala sikap siswa. Metode penelitian yang digunakan quasy experiment dengan desain Randomized Control Group Pretest-Posttest dan metode deskriptif. Berdasarkan analisis CRI diperoleh kuantitas miskonsepsi pada kelas eksperimen lebih kecil dibanding kelas kontrol. Hasil skala sikap siswa menyatakan hampir seluruh siswa setuju bahwa pembelajaran konseptual interaktif berbantuan cmaptools dapat meningkatkan pemahaman konsep.